The Analysis of Comparison Electrical Power Measurement on LED Lamps - Prisma Megantoro; Geston Bakti Muntoha; Kunal Kunal; Phong Thanlr Nguyen; Elsaved Helmy (Journal of Robotics and Control (JRC), 2020)
Abstract— This study uses 2 variations of the value of the DC 12V LED lamp power that is 12W and 15W with 3 different brands of lamp variations. Measurement of input voltage and current is carried out using a Krisbow KW06-490 DC clampmeter that has been calibrated as a standard measuring instrument and a Krisbow KW06-491 DC clampmeter that has not been calibrated as a test gauge 1 and a Multimeter Viper DT830B that has not been calibrated as a test gauge 2. Data the current and input voltage between each lamp and different lamp brands are used to calculate the value of the test lamp power and then compare it.The big conclusion from this study was found that the error value between the value of the test power or the use of DC 12V LED lamps with 12W written power on R, S, and T brand lamps was ± 51.67%, ± 70.75%, ± 61.33 %. In 15W lamps the brands R, S, and T were ± 7.20%, ± 0.53%, ± 8.27%.